Analysis of Colonization Ability of Six Biocontrol Bacteria in Cucumber Plants under Chemical Stress Condition - Li ZHENG; Jiehao HUANG; Hongxia LIU; Yuming LUO; Jianhua GUO (Guangdong nongye kexue, 2022)
【Objective】The study was carried out to explore the effect of chemical stress on the colonization ability of biocontrol bacteria on cucumber plants.【Method】By setting a greenhouse experiment and two field experiments, biocontrol bacteria were inoculated on cucumber plants without fungicides and pathogens, with fungicides and without pathogens, with fungicides and pathogens, respectively.【Result】The six biocontrol strains tested had good colonization effects on cucumber leaves and roots. Under the greenhouse conditions without fungicides and pathogens, the colonization of each biocontrol strain showed a trend of decrease-increase-stability, strains 1BS4 and 3BY4 had strong colonization ability in cucumber leaves and roots. The colonization quantity of strains 1BS4 and 3BY4 was close to 106 CFU/g(FW) at 30 days post inoculation(dpi) about 104 CFU/g(FW); Under the field conditions without fungicides and with pathogens, there were significant differences in the colonization quantities of various biocontrol strains in leaves and roots, and they all showed a trend of decrease-increase-decrease-stability. Strain 5BJN1 had the strongest colonization ability. The colonization quantity of cucumber leaves and roots at 30 dpi was 105.92 CFU/g(FW) and 104.95 CFU/g(FW), respectively; Under the field conditions with both fungicides and pathogens, there were differences in the colonization quantity of biocontrol bacteria in leaves and roots, but the difference was not significant, and all showed a trend of decrease-increase-decrease-stability, and the colonization quantities of strains 3BJN7 and 5BJN1 in cucumber leaves at 30 dpi were relatively high, which were 103.88 CFU/g(FW) and 104.23 CFU/g(FW), respectively. The colonization quantity of other strains was about 103 CFU/g(FW).【Conclusion】The effect of chemicals on the colonization ability of biocontrol bacteria depends on the types of strains. Some strains (3BJN7 and 5BJN1) have good compatibility with chemicals. In the presence of cucumber downy mildew, they can still maintain a certain amount of colonization after using chemicals, therefore, they can be used as potential biocontrol agents; In the absence of fungicide stress, the emergence of downy mildew pathogen can induce the improvement of colonization ability of strain 3BJN7 so that it can colonize stably on cucumber plants.